2001
DOI: 10.1103/physreva.64.043413
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced double ionization with circularly polarized light

Abstract: Using 120-fs, 800-nm Ti:sapphire laser pulses, ionic yields of singly and doubly charged magnesium ions were measured as a function of intensity and laser field ellipticity. A clear ''nonsequential'' enhancement of the doubly charged ion is observed for circularly polarized light in addition to linearly polarized light. Over the entire intensity range the double-ionization yield is considerably higher for linear polarization than it is for circular polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 27 publications
13
69
2
Order By: Relevance
“…We believe that also in atoms the first emitted electron may influence the parent ion, such that the averaged ionization probability for the second ionization step is higher than predicted by SDI. An enhanced ion count rate of doubly charged magnesium ions in circularly polarized light has already been reported 20 . However, the count rate statistics of this measurement is insufficient to make an equivalent statement about our measurement.…”
Section: Early Release Of the Second Electronmentioning
confidence: 98%
“…We believe that also in atoms the first emitted electron may influence the parent ion, such that the averaged ionization probability for the second ionization step is higher than predicted by SDI. An enhanced ion count rate of doubly charged magnesium ions in circularly polarized light has already been reported 20 . However, the count rate statistics of this measurement is insufficient to make an equivalent statement about our measurement.…”
Section: Early Release Of the Second Electronmentioning
confidence: 98%
“…A particularly sensitive test for the existence of rescattering is a comparison between ion yields obtained using linearly and circularly polarized light. In a circularly polarized field, the electron tends to orbit the core rather than recollide, causing a dramatic suppression of ion yields in double ionization [8].…”
mentioning
confidence: 99%
“…The seemingly complete lack of a PES plateau region is further discussed in Ref. �12�,where Gillen et al demonstrated that, based on ionization rate ellipticity studies, rescattering does not appear to be as dominant an ionization mechanism for magnesium as it is for the noble gases.…”
Section: A General Pes Characteristicsmentioning
confidence: 97%